The Association Between Social Outsiderhood and School Absence is Mediated by Internalizing Symptoms - Alanko, Katarina; Söderberg, Patrik; Lagerström, Martin; Laakso, Mikko-Jussi; Junttila, Niina (Springer Science and Business Media LLC, 2026)
Internalizing symptoms and school absenteeism often co-occur. This study explores their detailed associations and examines whether internalizing symptoms (depression and anxiety) mediate the relationship between social outsiderhood (loneliness and ostracism) and school absence. It also investigates the links between various types of school absence (truancy, emotion-based absence, school withdrawal, and school exclusion) and experiences of loneliness and/or ostracism. Data were collected from 1,866 Finnish middle school adolescents (M age = 14.95, SD = 0.86). Findings indicate that both loneliness and ostracism are associated with school absences, with internalizing symptoms serving as a mediator, however, with a low effect size (indirect association: β = 0.05 and β = 0.02 respectively), implying that other factors contribute to school absences too. Students experiencing school exclusion reported the highest levels of social outsiderhood. These results underscore the importance of addressing students’ social situations when assessing school absence and developing preventive interventions within the school context.